The Role of Beyond Budgeting Entry Scan in Local Government Budgeting: A Case Study of Stunting Handling in North Toraja Regency - Palimbong, Frederik Victor; Pasoloran, Oktavianus; Tanamal, Cherly Elisabeth; Sampe, Ferdinandus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
The study aimed at investigating the role of beyond budgeting entry scan in handling stunting health problem in North Toraja Regency. Descriptive qualitatitave approach was applied to the study. Population of the study were government officers both in financial and health sector. In depth interview was deployed to collect data. Content analysis, which describing answers based on existing theories was applied to analyze the collected data. The results reveal the implementation of stunting management in North Toraja regency focus on synergetic policies between the central, regional and village government. The beyond budgeting entry scan for stunting management in North Toraja Regency improves governmental value in form of decreasing in stunting cases and improves local government programs succes. It is suggested for future research to include wider population and to identify the best strategy in acclerating stunting reduction.